Learning Strategies at SD 8 Muhammadiyah Reinforcement during the Covid-19 Pandemic - Friska Aprilia; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This research is motivated by the regulation of the Ministry of Education and Culture regarding the implementation of education during Covid-19 pandemic which requires the implementation of distance learning using online learning media. The purpose of this study was to find out the history of school formation, differences in learning before and after pandemic, challenges faced and learninf strategies implemented by SD 8 Muhammadiyah Tulangan during Covid-19 pandemic. The method used is qualitative with the observation, interview, question and answer. The results of thsi study can be concluded that SD 8 Muhammadiyah has a combination of learning strategies between face to face learning and online learning or what is commonly referred to blended learning method. The blended learning methods that is implemented in SD 8 Muhammadiyah Sidoarjo are conducting learning activities through zoom application for better material delivery and conducting study visits to students’ homes directly to share opinions and views between teacher, parents, and students as well as to find out advantages and disadvantages of online learning so far.